How to adaptively balance ‘classic’ or ‘conservative’ approaches in tooth defect management: a 3D-finite element analysis study - Jiani Xu; Xu Liang; Lili Hu; Chen Sun; Zhipeng Zhang; Jiawei Yang; Jie Wang (BMC Oral Health)
Abstract Background The widespread adoption of resin-based composites has increased interest in minimally invasive treatment strategies that prioritize the preservation of sound dentin. While classic cavity preparation techniques remain clinically relevant, the optimal cavity design for ensuring restoration longevity and residual tooth structure integrity remains uncertain. This study aims to investigate the influence of cavity dimensions on the mechanical performance of resin composites and natural tooth structures using finite element analysis (FEA). By evaluating stress distribution across different cavity configurations, this study seeks to determine the optimal cavity design for various tooth defects, ultimately offering insights into effectively balancing conventional and conservative cavity preparation principles. Methods Twelve Class II cavity models with varying lengths (L), widths (W), and depths (D) were generated using a single extracted natural tooth. A vertical occlusal load of 500 N was applied, and interactions among the different model components were simulated using tie constraints. The distribution of maximum principal stress (MaxPS) was analyzed via static linear FEA. Results Medium-sized cavities exhibited relatively lower stress concentrations. The depth, width, and length of the cavities significantly influenced the MaxPS values. Notably, cavities with a depth of 2/3 demonstrated lower MaxPS values compared to both shallower and deeper counterparts (Dentin: W2/5-D3/4-L1: 61.499 MPa; W 2/5-D 2/3-L 1: 32.796 MPa; W 2/5-D 1/2-L 1: 38.724 MPa). Additionally, cavities with full-length configurations exhibited lower MaxPS values than those with 4/5-length designs (Dentin: W 2/5-D 4/5-L 1: 44.929 MPa; W 2/5-D 4/5-L 4/5: 73.362 MPa). Conclusion Cavity dimensions play a critical role in influencing stress distribution within both the restorative material and the tooth structure, underscoring the need to optimize cavity size. These findings support decision-making during cavity preparation, highlighting the trade-off between preserving tooth structure and ensuring mechanical stability. It is important to note that this approach should not be considered as a one-size-fit-all recommendation, but rather as a case-specific strategy tailored to the unique clinical conditions of each patient. Graphical Abstract